THE BEHAVIOR OF TRACE ELEMENTS DURING THE CHEMICAL EVOLUTION OF THE H2O-, B-, AND F-RICH GRANITE-PEGMATITE-HYDROTHERMAL SYSTEM AT EHRENFRIEDERSDORF, GERMANY: A SXRF STUDY OF MELT AND FLUID INCLUSIONS - Rickers K.; Thomas R.; Heinrich W. (My University, 2006)
Detailed melt and fluid inclusion studies in quartz hosts from the Variscan Ehrenfriedersdorf complex revealed that ongoing fractional crystallization of the highly evolved H2O-, B-, and F-rich granite magma produced a pegmatite melt, which started to separate into two immiscible phases at about 720°C, 100 MPa. With cooling and further chemical evolution, the immiscibilty field expanded. Two conjugate melts, a peraluminous one and a peralkaline one, coexisted down to temperatures of about 490°C. Additionally, high-salinity brine exsolved throughout the pegmatitic stage, along with low-density vapor. Towards lower temperatures, a hydrothermal system gradually developed. Boiling processes occurred between 450 and 400°C, increasing the salinities of hydrothermal fluids at this stage. Below, the late hydrothermal stage is dominated by low-salinity fluids. Using a combination of synchrotron radiation-induced X-ray fluorescence analysis and Raman spectroscopy, the concentration of trace elements (Mn, Fe, Zn, As, Sb, Rb, Cs, Sr, Zr, Nb, Ta, Ag, Sn, Ta, W, rare earth elements (REE), and Cu) was determined in 52 melt and 8 fluid inclusions that are representative of distinct stages from 720°C down to 380°C. Homogenization temperatures and water contents of both melt and fluid inclusions are used to estimate trapping temperatures, thus revealing the evolutionary stage during the process. Trace elements are partitioned in different proportions between the two pegmatite melts, high-salinity brines and exsolving vapors. Concentrations are strongly shifted by co ncomitant crystallization and precipitation of ore-forming minerals. For example, pegmatite melts at the initial stage (700°C) have about 1,600 ppm of Sn. Concentrations in both melts decrease towards lower temperatures due to the crystallization of cassiterite between 650 and 550°C. Tin is preferentially fractionated into the peralkaline melt by a factor of 2-3. While the last pegmatite melts are low in Sn (64 ppm at 500°C), early hydrothermal fluids become again enriched with about 800 ppm of Sn at the boiling stage. A sudden drop in late hydrothermal fluids (23 ppm of Sn at 370°C) results from precipitation of another cassiterite generation between 400 and 370°C. Zinc concentrations in peraluminous melts are low (some tens of parts per million) and are not correlated with temperature. In coexisting peralkaline melts and high-T brines, they are higher by a factor of 2-3. Zinc continuously increases in hydrothermal fluids (3,000 ppm at 400°C), where the precipitation of sphalerite starts. The main removal of Zn from the fluid system occurs at lower temperatures. Similarly, melt and fluid inclusion concentrations of many other trace elements directly reflect the crystallization and precipitation history of minerals at distinctive temperatures or temperature windows. © Springer-Verlag 2006.
Keywords: EHRENFRIEDERSDORF; FLUID INCLUSIONS; GERMANY; MELT INCLUSIONS; SN-W DEPOSIT; SYNCHROTRON RADIATION XRF